Nimrod: Lutheran Pastor/Hunters in Texas. (December 2017) - Hoerig, Karl A.
Each fall from 1984 to 2007 a group of Lutheran pastors in Texas gathered at the ranch of another pastor to hunt white-tailed deer during the opening week of the annual hunting season. Called "Nimrod" after the ancient Babylonian king identified in the Bible as "a mighty hunter before the Lord" (Genesis 10:9), also an acronym for "November Invitational Ministerial Recreational Outdoor Diversion, " the event provided opportunities for recreation and fellowship for active and retired clergy, centered around the hunt. To the casual observer hunting is not an immediately obvious pastime to bring Christian ministers together. This ethnographic study examines the place of hunting within Christian theology and explores how the annual deer hunting retreat in fact created an ideal opportunity for clergy to escape from the social constraints of their professional lives while engaging in the deeply meaningful practice of harvesting wild game.